دراسة تحليلية للسياحة الداخلية في الجزائر للفترة (2000 - 2024) - قلعي ،كريمة; أوسعديت، أمال (University of Eloued جامعة الوادي, 2025)
يهدف هذا البحث لدراسة وتحليل واقع السياحة الداخلية في الجزائر وأثارها الاقتصادية في رفع معدل الناتج المحلي للدولة وتحقيق تنمية سياحية مستدامة وخلق فرص عمل، حيث تم تحليل السياحة الداخلية في الفترة (2020-2024) من خلال أنواعها (السياحة الحموية، السياحة الساحلية، السياحة الصحراوية)، توصلت نتائج دراستنا أن قطاع السياحة في الجزائر بأنواعها لم تحقق ارتفاعا خلال السنوات (2021،2021)، بسبب جائحة كورونا ومنح السواح من الدخول، بينما حققت انتعاشا وارتفاعا ملحوظا خلال سنة 2024 في الجزائر خصوصا في السياحة الساحلية بشكل أكبر من أجل الاستجمام، اضافة الى السياحة الصحراوية لهدف العلاج من خلال رمال الصحراء والمياه المعدنية. على الرغم من أن الجزائر سعت للنهوض بالقطاع السياحي وحققت تطورا إلا أنها واجهت العديد من المعيقات. This research aims to study and analyze the reality of domestic tourism in Algeria and its economic impact on raising the country's GDP, achieving sustainable tourism development, and creating job opportunities. Domestic tourism was analyzed for the period (2020-2024) according to its types (thermal tourism, coastal tourism, and desert tourism). The results of our study concluded that the tourism sector in Algeria, in all its types did not achieve growth during the years (2021-2021), due to the COVID-19 pandemic and the decline in tourist income. However, it achieved a remarkable recovery and increase in 2024 in Algeria, particularly in coastal tourism, primarily for recreation, in addition to desert tourism for therapeutic purposes, using desert sands and mineral waters. Although Algeria has sought to advance the tourism sector and achieved progress, it has faced many obstacles.
An analytical study of domestic tourism in Algeria for the period (2000 - 2024)
مقال
Keywords: السياحة; السياحة الداخلية; السياحة الحموية; السياحة الساحلية; السياحة الصحراية; Tourism; domestic tourism; thermal tourism; coastal tourism; desert tourism.